Mouse Nerve Growth Factor Injection and Progression Rate in Patients With Amyotrophic Lateral Sclerosis: An Observational Study - Li, Jia-Tong; Dong, Si-Qi; Qian, Ting; Yang, Wen-Bo; Chen, Xiang-Jun (Frontiers in Neurology, 2022)
Objectives: Amyotrophic lateral sclerosis (ALS) is a progressive, fatal disease with no curative treatment up to now. This study aims to analyze ALS progression of patients treated with mouse nerve growth factor (mNGF), as well as the effects, side effects and adverse events of the therapy. Materials & Methods: A retrospective, observational study was performed including 94 ALS patients from July 2020 to July 2021. Thirty two of them were treated with at least one course of mNGF on a regular riluzole use, and the rest 62 were treated with riluzole only. The declining rates of BMI and ALSFRS-R score were compared between the two groups to indicate ALS progression. Results: No significant differences on ALS progression indicated by the declining rates of BMI and ALSFRS-R score were observed between the two cohorts. ALS progression before and after the first treatment course of mNGF also showed no discernible difference. However, we noticed a moderate 62.7% and 25.1% reduction in the declining rate of BMI and ALSFRS-R motor subscore when comparing mNGF+riluzole treatment to riluzole only. The mNGF treatment was overall safe and well-tolerated, and a rare case of diarrhea was reported after mNGF injection. Conclusions: Our study revealed that mNGF treatment was overall safe and well-tolerated in ALS patients. Application of mNGF combined with regular riluzole treatment had no significant clinical effects on delaying ALS progression. Prospective cohort studies and randomized clinical trails based on larger cohorts and longer follow-up time are needed to make a more convincing conclusion.